The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1111/j.1476-5381.1996.tb15253.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical and behavioural interactions between ibogaine and nicotine in the rat

Abstract: 1 In vivo brain microdialysis has been employed to investigate the effects of ibogaine on nicotineinduced changes in dopamine overflow in the nucleus accumbens (NAc) of freely moving rats. The effects of the compound on locomotor responses to nicotine and behaviour in the elevated plus-maze were also examined. 2 No changes were observed in the dopamine overflow or the locomotor activity of the animals following the administration of ibogaine (40 mg kg-', i.p.). However, ibogaine, administered 22 h earlier, sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 32 publications
(41 reference statements)
1
19
0
1
Order By: Relevance
“…Dopamine receptor antagonists and 6OHDA lesions of the mesolimbic pathway have been found to decrease intravenous self-administration of nicotine in rats (Corrigall and Coen 1991;Corrigall et al 1992). In the present study, in accordance with previous data from other laboratories (e.g., Imperato et al 1986;Damsma et al 1989;Brazell et al 1990;Benwell et al 1996) as well as from this laboratory 277 Fig. 4 E¤ects of 18-MC (n = 6 / dose), administered 15 min before a 1-h test session, on total responses ( % of baseline; mean±SEM) and % nicotine preferences (mean ± SEM) of rats self-administering nicotine; an asterisk indicates signiÞcant (P < 0.050.01) di¤erences from 0 dose (saline) Fig.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Dopamine receptor antagonists and 6OHDA lesions of the mesolimbic pathway have been found to decrease intravenous self-administration of nicotine in rats (Corrigall and Coen 1991;Corrigall et al 1992). In the present study, in accordance with previous data from other laboratories (e.g., Imperato et al 1986;Damsma et al 1989;Brazell et al 1990;Benwell et al 1996) as well as from this laboratory 277 Fig. 4 E¤ects of 18-MC (n = 6 / dose), administered 15 min before a 1-h test session, on total responses ( % of baseline; mean±SEM) and % nicotine preferences (mean ± SEM) of rats self-administering nicotine; an asterisk indicates signiÞcant (P < 0.050.01) di¤erences from 0 dose (saline) Fig.…”
Section: Discussionsupporting
confidence: 95%
“…While preclinical studies in rats have found it to decrease morphine , cocaine (Cappendijk and Dzoljic 1993;Glick et al 1994), and alcohol (Rezvani et al 1995) self-administration, only neurochemical interactions of ibogaine with nicotine have been reported. Ibogaine blocks nicotine-induced dopamine release in the nucleus accumbens (Benwell et al 1996;Maisonneuve et al 1997), similar to its e¤ect on dopamine release induced by morphine (Maisonneuve et al 1991). 18-Methoxycoronaridine (18-MC), a novel iboga alkaloid congener, has e¤ects that mimic those of ibogaine on morphine and cocaine self-administration (Glick et al 1996a) and on alcohol intake (Rezvani et al 1997); however, 18-MC does not produce the typical side e¤ects (e.g., tremor, decreased motivated behavior in general) and toxicity (cerebellar Purkinje cell loss) associated with ibogaine (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Eleven of the 13 published preclinical studies of iboga alkaloids in opioid withdrawal indicate a significant attenuation of opioid withdrawal signs in the rat (Dzoljic et al, 1988;Sharpe and Jaffe, 1990;Maisonneuve et al, 1991;Glick et al, 1992;Cappendijk et al, 1994;Rho and Glick, 1998;Parker et al, 2002;Panchal et al, 2005), mouse (Frances et al, 1992;Popik et al, 1995;Layer et al, 1996;Leal et al, 2003), and primate (Aceto et al, 1992). Iboga alkaloids are also reported to reduce the self-administration of morphine Glick et al, 1994;Glick et al, 1996;Maisonneuve and Glick, 1999;Pace et al, 2004), cocaine (Cappendijk and Dzoljic, 1993;Glick et al, 1994), amphetamine , methamphetamine (Glick et al, 2000;Pace et al, 2004), alcohol (Rezvani et al, 1995;Rezvani et al, 1997;He et al, 2005) and nicotine Glick et al, 2000), and to diminish dopamine efflux in the nucleus accumbens (NAc), which is regarded as a correlate of drug salience (Berridge, 2007), in response to opioids Glick et al, 1994;Glick et al, 2000;Taraschenko et al, 2007b) or nicotine (Benwell et al, 1996;Glick et al, 1998).…”
Section: Preclinical Researchmentioning
confidence: 92%
“…Ibogaine also reduces mice's preference for cocaine when they are given a choice between either water or a solution containing the drug (37). Ibogaine has been reported to antagonize the locomotor effects induced by cocaine (38), nicotine (39), and amphetamine in mice (40). Furthermore, ibogaine effectively blocks methamphetamine-induced hyperthermia in mice (41).…”
Section: Tabernanthe Iboga and Voacanga Africanamentioning
confidence: 92%